Data Gathering: Biased in Psychosis? - Van Dael, Frank (Oxford University Press, 2006)
This study examined whether the probabilistic reasoning bias referred to as a “jumping-to-conclusions” (JTC) style of reasoning, which, according to previous research, is associated with particular psychotic symptoms such as delusions, represents a trait that can also be detected in nonpsychotic relatives of patients with schizophrenia and in nonpsychotic individuals with a high level of psychotic experiences. Participants were, in order of level of psychosis liability, 40 patients with schizophrenia or a schizoaffective disorder, 40 first-degree nonpsychotic relatives, 41 participants from the general population with above average expression of psychotic experiences, and 53 participants from the general population with an average level of psychotic experiences. A “jumping-to-conclusions” bias was assessed using the beads task. A dose-response relationship was found in the association between level of psychosis liability and JTC (defined as needing only a single bead to complete the beads task) (odds ratio [OR] linear trend = 1.59, 95% CI: 1.13–2.24), and, independently, alinear association was apparent between JTC and level of delusional ideation (OR linear trend = 2.59, 95% CI: 1.18–5.69). In addition, the association between psychosis liability and JTC was generally much stronger as the level of delusional ideation was higher. JTC is associated with liability to psychosis (trait), in particular if the psychosis phenotype is characterized by delusional ideation (state).